VISUAL ACUITY ASSESSMENT WITH ATROPINE PENALIZATION VS PARTIAL OCCLUSION THERAPY IN AMBLYOPIA PATIENTS IN SOUTH PUNJAB - MUZAMIL, M; MAJEED, B; ATTAULLAH, .; RAO, MRQ; TAYYAB, F; BATOOL, H (Biological and Clinical Sciences Research Journal, 2023)
A retrospective study was conducted in the Ophthalmology Department of Nishtar Medical Hospital from September 2022 to September 2023 to compare the effectiveness of atropine penalization and occlusion therapy in treating amblyopia in children. The study included 50 children aged 2-9 years with no prior treatment history of amblyopia. The children were divided into two groups: Group A received atropine penalization, while Group B received occlusion therapy. Both groups had a mean age of 5.5 years, and all patients passed the visual acuity tests. Strabismus was high in both groups, with 96% in Group A and 92% in Group B. The treatment duration in Group A was 7.5 months on average, while it was 4.5 months in Group B. Treatment compliance was higher in Group A (96%) compared to Group B (68%). After the treatment, the atropine group had a visual acuity range of 6/6 to 6/60, with a mean visual acuity of 6/10. On the other hand, the occlusion group had a visual acuity range of 6/6 to 6/120, with a mean visual acuity of 6/20. The study concluded that atropine penalization had better patient outcomes and compliance in treating amblyopia in pediatric patients. The study concluded that atropine penalization had better patient outcomes and compliance in treating amblyopia in pediatric patients.